Growth and production of upland rice (Oryza sativa L.) in ultisol using liquid organic fertilizer and NPK - Effendi, Arman; Gusmawartati; Rosnia (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
One of the efforts to increase rice production in the dry land of ultisol such as in Riau is extensification. To alter low nutrient availability in ultisol, liquid organic fertilizer (LOF) from waste of banana corm and NPK fertilizers are evaluated. Research aimed to obtain the best dose of LOF and NPK fertilizers to improve the productivity of upland rice on ultisols. This experiment was arranged in a completely randomized factorial design consisting of two factors. The first factor was LOF from banana corm (0 mL, 50 mL, 100 mL, and 150 mL per polybag). The second factor was NPK fertilizers (0%, 25%, 50%, and 100% recommendation dose); the recommendation base was: 300 kg Urea, 100 kg TSP, and 100 kg KCl ha-1. The results indicated that the application of 150 mL LOF per polybag and NPK fertilizers at 100% recommendation significantly enhances plant height, number of tiller numbers, productive tiller, filled grain per panicle, and dry grain weight of Inpago 9 variety. Keywords: rice; organic matter; inorganic; sub-optimal soil